1964
DOI: 10.1126/science.143.3605.471
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Growth Inhibitors Produced by Aromatic Shrubs

Abstract: Root growth of Cucumis and Avena seedlings is inhibited by volatile materials produced by leaves of Salvia leucophylla, S. apiana, and Artemisia californica. The toxic substance may be deposited when dew condenses on affected seedlings in the field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
0
2

Year Published

1976
1976
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(97 citation statements)
references
References 3 publications
1
94
0
2
Order By: Relevance
“…He eventually showed that grazing, trampling or seed feeding activities of animals resulted in bare concentric areas surrounding Salvia shrubs. This finding, which discounted the highly cited study of Muller et al (1964), proved a major setback to allelopathy research and resulted in considerable criticism of allelopathy by certain prominent ecologists. John Harper (1977) was one ecologist who reported that, ''Almost all species can, by appropriate digestion, extraction and concentration, be persuaded to yield a product that is toxic to one species or another.''…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…He eventually showed that grazing, trampling or seed feeding activities of animals resulted in bare concentric areas surrounding Salvia shrubs. This finding, which discounted the highly cited study of Muller et al (1964), proved a major setback to allelopathy research and resulted in considerable criticism of allelopathy by certain prominent ecologists. John Harper (1977) was one ecologist who reported that, ''Almost all species can, by appropriate digestion, extraction and concentration, be persuaded to yield a product that is toxic to one species or another.''…”
Section: Introductionmentioning
confidence: 98%
“…The identification of allelopathy as the potential cause of vegetation patterning however, proved difficult due to the dynamic nature of soil and complex ecosystem interactions. Muller et al (1964) first reported that zones of inhibition around shrubs such as Salvia leucophylla, Artemisia californica and Adenostoma fasciculatum were likely due to volatile chemicals released by these shrubs. Bartholomew (1970), however, ruled out the possibility of allelopathy as a potential cause for these zones by creating barriers restricting mammalian movement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bare zone between mature chaparral or coastal sage scrub and grassland, possibly controlled in part by allelopathic inhibition (Muller et al 1964), owes its existence on some sites to rodent and rabbit predation (Fig. 3.7) (Bartholomew 1970).…”
Section: Rodents and Plant Community Structurementioning
confidence: 99%
“…For example, methanol appears to be a volatile routinely released from plant leaves and it probably is a carbon source for methylobacteria that colonize leaf surfaces (49,50), yet we have no information about its effects on adjacent plants. In contrast, volatile phytotoxic monoterpenes such as cineole, piene, and camphor have long been reported as allelopathic inhibitors (51)(52)(53)(54).…”
Section: Allelochemical Release and Transfersmentioning
confidence: 99%